Screening For Cervical Cancer Among Adult Women: A Self-Reported Nationwide Study In Ghana - Nuertey, B.D.; Ansong, J.; Nartey, E.B.; Hodgson, A.; et al. (BMC Women's Health, 2025)
Background Cervical cancer remains a significant global health challenge, despite advancements in screening and treatment. As one of the most preventable and curable cancers, its burden disproportionately affects women in low and middle-income countries where access to screening programs and healthcare services is limited. Screening for cervical cancer has evolved significantly over the decades, with the advent of cytology-based Pap smears and more recently, human papillomavirus (HPV) testing, offering improved sensitivity and specificity in detecting precancerous lesions. Effective screening programs have led to a substantial reduction in cervical cancer incidence and mortality in many high-income countries. However, disparities persist due to variations in healthcare infrastructure, socioeconomic factors, and awareness levels among women. This manuscript explores uptake of screening test, type of tests and barriers to periodic uptake of screening among adult women in Ghana. Methods A nationwide survey was conducted, using a nationally representative sample of 3,326 women aged 18 to 69, and the data were analyzed using Stata 17. The study forms part of the WHO STEPwise approach to NCD risk factor surveillance (STEPS). Results The results showed generally low screening uptake, particularly among women aged 30–49, who are considered a high-risk group. The HPV-DNA test (70.42%) was the most reported screening method, while 29.58% of women were screened using the Pap smear. The primary barrier to screening uptake was a lack of knowledge about how or where to access testing services. Conclusion The study highlights the need for increased community awareness and education on cervical cancer screening. Integrating cervical cancer screening education into routine sexual and reproductive health programs offers a promising approach to raising awareness and improving uptake, which could help reduce the burden of cervical cancer in Ghana.
Research Article
Keywords: Cervical cancer; Screening; Self-report; Adult women; Ghana